1970
DOI: 10.1177/070674377001500102
|View full text |Cite
|
Sign up to set email alerts
|

The Place of Thiothixene in the Treatment of Schizophrenic Patients

Abstract: The drugs used in this study were supplied through the courtesy of Pfizer Limited,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1972
1972
1978
1978

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Thiothixene is a well-known thioxanthen derivative with a piperazine sidechain. The drug has documented antipsychotic efficacy (Sterlin et al (1970), Kellam & Jones (1971), Lee & Simpson (1973)) without unwanted sedative effects. It is mainly recommended for long-term treatment of chronic psychotic conditions where an unspecific sedative effect is not wanted.…”
mentioning
confidence: 99%
“…Thiothixene is a well-known thioxanthen derivative with a piperazine sidechain. The drug has documented antipsychotic efficacy (Sterlin et al (1970), Kellam & Jones (1971), Lee & Simpson (1973)) without unwanted sedative effects. It is mainly recommended for long-term treatment of chronic psychotic conditions where an unspecific sedative effect is not wanted.…”
mentioning
confidence: 99%
“…Previous studies have shown thiothixene to be efficacious in relieving the symptoms of acute schizophrenic patients (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…A favourable feature of thiothixene is that it causes side effects and adverse reactions to a much smaller extent than other neuroleptics (3,10,22).…”
mentioning
confidence: 99%
“…Under thiothixene treatment these patients become more animated, they achieve more ac tive interest in, and better emotional contact with, the environment (3,13,14,22).…”
mentioning
confidence: 99%